Histomorphological and histochemical Study of the jejunum in moorhen (Gallinula chloropus) in Iraq - Rafal Yousuf; Azhar saleem Khalaf (University of Thi-Qar Journal of agricultural research, 2023)
The goal of the current investigation was to gather information on the histology and histochemical composition of the jejunum in moorhens (Gallinula chloropus). In order to conduct the current investigation, six moorhens were gathered. They were purchased from regional vendors in particular markets in Baghdad, Iraq. To collect the intestine, birds were put down after being dissected, and the specimens were then fixed in 10% neutral buffered formalin. The blocks were sectioned at 6 m thickness and stained with Mayer's hematoxylin and eosin, Masson trichrome stain, periodic acid Schiff reagent (PAS), and Alcian blue stain (AB)PH-2.5 ,after being thoroughly fixed. The specimens were then cleared in xylene and embedded in paraffin wax. According to the Gross findings, the small intestine is made up of the duodenum, the jejunum, and the ileum. Histologically, the mucous membrane was thrown into large numerous villi in the jejunum, showing blunt apical part and wide basal part with thin layer of muscularis mucosa. The submucosa was thin layer of connective tissue. Below the submucosa was thick layer arranged in a thick circular and thin longitudinal. According to histochemical results, the PAS stain had a negative reaction on columnar cells while having a positive reaction on goblet cells. When the AB (pH 2.5) was applied, the wall displayed epithelial cells that stained negatively while the goblet cells responded favorably to their acidic mucopolysaccharides.